HIV Status Disclosure and Sexual Transmission Risks among People who are Living with HIV and Receiving Treatment for Non-HIV Sexually Transmitted Infections, Cape Town, South Africa - Kalichman, Seth (J Acquir Immune Defic Syndr, 2020)
BACKGROUND: HIV status disclosure to sex partners potentially reduces the risk of sexually transmitting HIV. However, there is limited information on the associations between HIV status disclosure in types of sexual partnerships and ensuing sexual practices. METHODS: We examined HIV status disclosure to sex partners among 205 men and women living with HIV and receiving diagnostic and treatment services for a co-occurring sexually transmitted infection (STI) in Cape Town, South Africa. Participants completed partner-by-partner sexual behavior interviews and provided permission to extract recurrent STI clinic visits over the subsequent 12-months. RESULTS: Three groups were formed on the basis of HIV status disclosure to sex partners: (a) 22% reported only HIV same-status partners; (b) 26% had HIV negative or unknown HIV status (HIV different-status) sex partners to whom they had disclosed their HIV status; and (c) 52% had at least one HIV different-status partner to whom they had not disclosed. There were no associations between HIV status disclosure and demographic characteristics, sexual practices, or recurrent STI clinic visits. Undisclosed HIV to at least one HIV different-status sex partner was associated with greater alcohol use and less likelihood of receiving ART; participants who were least likely to disclosure their HIV status to partners drank more alcohol and were less likely to be taking antiretroviral therapy. CONCLUSIONS: High prevalence of partner non-disclosure and lack of significant correlates to HIV status disclosure indicate a need for further research with an eye toward identifying disclosure processes and mechanisms that may ultimately lead to effective interventions.